Epidemiology of cleft lip and cleft palate in Gorgan, 1998-2003 - MJ Golali Pour (Babol University of Medical Sciences, 2005)
Background and Objective: Cleft lip and palate is one of the most common human congenital craniofacial abnormalities with the side effects of middle-ear infections, hard of hearing, nutritional problems, speaking, and other societal burdens. The objective of this study was to assess the frequency of cleft lip and palate and its relation with sex, ethnic group, paternal and maternal age, consanguineous marriage and season in Gorgan during 6 years. Methods: This cross-sectional study was done on 37951 births in Gorgan’s Dezyani hospital during 1998-2003. Sex, type of abnormalities, ethnic group, paternal and maternal age, consanguineous marriage, season and date of birth were recorded in questionnaires and data were analyzed by SPSS. Findings: The prevalence of cleft lip and cleft palate was 0.97 per 1000 birth and it was more common in males (1.08 per 1000) than in females (0.86 per 1000). The rate of cleft was 0.86, 0.89 and 1.47 per 1000 in native Fars, Turkaman and Sistani ethnic group, respectively. 29.7% of parents had consanguineous marriage. 29.7% of mothers with affected newborns consumed different drugs during pregnancy. The commonest rate was in winter and autumn. Maternal and paternal age was 35.5 and 28.5 years, respectively. Cleft was more common in 1998. Conclusion: This study reveals that incidence of cleft in Gorgan is much closer to European and east Asian countries. Consanguineous marriage and the toxicity of pregnant women with drugs or chemicals can induce cleft palate.